“No one will say homemakers don’t work” A study in Dhaka city to explore the perceptions of women on redefining unpaid work: Recognition or redistribution? (Social Science Review, 2023)
This article analyses the multiple dynamics of getting recognition for unpaid work based on the perceptions and expectations of both employed and non- employed women from middle and lower middle class in Dhaka city. The study follows qualitative research methodology through conducting semi structured in- depth interviews with 40 married women. The findings underscore that women’s perceptions on unpaid work are widely diverse and depend on their economic class and employment status. Still a good number of women believe that they are born to do unpaid work and women should not demand any financial benefits in return of their care and domestic work. Besides, there is a few women who strongly support the idea of wage creation for unpaid work, either from state, husband or from both. A huge difference has been identified between the amount of money argued from different categories of women based on their economic class, employment status and other conditions of life. The findings also unfold wage creation is not sufficient to ensure the social recognition for women’s housework. Strong family bonding, respect, appreciation, happiness, and leisure can be the alternative ways of social recognition for unpaid work. Moreover, women also demand for men’s participation in the unpaid work.Social Science Review, Vol. 39(1), June 2022 Page 15-34